Structure of the hypusinylated eukaryotic translation factor eIF-5A bound to the ribosome - Schmidt, Christian (Nucleic Acids Res, 2016)
During protein synthesis, ribosomes become stalled on polyproline-containing sequences, unless they are rescued in archaea and eukaryotes by the initiation factor 5A (a/eIF-5A) and in bacteria by the homologous protein EF-P. While a structure of EF-P bound to the 70S ribosome exists, structural insight into eIF-5A on the 80S ribosome has been lacking. Here we present a cryo-electron microscopy reconstruction of eIF-5A bound to the yeast 80S ribosome at 3.9 Å resolution. The structure reveals that the unique and functionally essential post-translational hypusine modification reaches toward the peptidyltransferase center of the ribosome, where the hypusine moiety contacts A76 of the CCA-end of the P-site tRNA. These findings would support a model whereby eIF-5A stimulates peptide bond formation on polyproline-stalled ribosomes by stabilizing and orienting the CCA-end of the P-tRNA, rather than by directly contributing to the catalysis.